CONTEMPORARY CAPITALISM, CRISIS, AND THE POLITICS OF FICTION literature beyond fordism. - del Valle Alcalá, Roberto ([S.l.] : ROUTLEDGE, 2020)
Contemporary Capitalism, Crisis, and the Politics of Fiction: Literature Beyond Fordism proposes a fresh approach to contemporary fictional engagements with the idea of crisis in capitalism and its various social and economic manifestations. The book investigates how late-twentieth and twenty-first-century Anglophone fiction has imagined, interpreted, and in most cases resisted, the collapse of the socio-economic structures built after the Second World War and their replacement with a presumably immaterial order of finance-led economic development. Through a series of detailed readings of the words of authors Martin Amis, Hari Kunzru, Don DeLillo, Zia Haider Rahman, John Lanchester, Paul Murray and Zadie Smith among others, this study sheds light on the embattled and decidedly unstable nature of contemporary capitalism.
OCLC-licensed vendor bibliographic record.
Keywords: Capitalism and literature; Capitalism in literature; English literature -- 20th century -- History and criticism; English literature -- 21st century -- History and criticism; LITERARY CRITICISM / Feminist